29th Street.
Frank Pesce was born under a lucky star and has led a charmed life ever since. His luck, however has been both a blessing and a curse. born in New York's Italian American neighborhood of 29th Street, Frank has had the kind of luck that often he himself was not even aware of - but everyone else was. In particular, his father both loves and resents his youngest offspring's importable good fortune. And this causes constant friction between father and son. Frank's reputation for luck follows him everywhere, and he quickly becomes known in the neighborhood as an unbeatable card shark. Everyone, including the local toughs, sees Frank as a winner. But when he becomes one of the 500 finalists in New York State Lottery, Frank is forced to make a tough decision that puts his loyalty and love of family to the test.